Ready‐to‐eat street food: a potential source for dissemination of multidrug‐resistant Escherichia coli epidemic clones in Quito, Ecuador. (8th January 2020) - Zurita, J.; Yánez, F.; Sevillano, G.; Ortega‐Paredes, D.; Paz y Miño, A.
Abstract: Ready‐to‐eat food contamination with ESBL‐producing Escherichia coli is a growing health concern. Some of these strains also are epidemic clones and can cause community‐associated infections that are difficult to treat. In this study, the occurrence of ESBL‐producing E. coli contaminated ready‐to‐eat street food in Quito, Ecuador was evaluated. In total, 150 samples were collected randomly in the most crowded sites of the city. In all, 34 samples (34/150; 22·6%) were positive for total thermotolerant (44·5°C) coliforms resistant to cefotaxime. MALDI‐TOF analysis identified that the E. coli was found in 20 food samples (20/34; 59%). ESBL gene bla CTX‐M‐55 was identified in nine isolates, bla CTX‐M‐15 in six isolates, bla CTX‐M‐14 in two isolates, and one isolate each harboured bla CTX‐M‐24, bla CTX‐M‐65, bla CTX‐M‐55 and bla CTX‐M‐8 . Phylogenetic groups like A and B1 were the most common, followed by groups D and B2. MLST analysis identified 12 different sequence types (STs), the most common was ST162. Recognized epidemic clonal groups ST410, ST131 and ST744 were encountered. Ready‐to‐eat street food is a potential way of spreading ESBL‐producing E. coli epidemic clones in Quito, Ecuador. Significance and Impact of the Study: This study identified ESBL‐producing Escherichia coli epidemic clones: ST131, ST410 and ST744 in ready‐to‐eat street food samples. Street food is a possible way to spread harm multidrug‐resistant (MDR) E. coli strains in the community. Studies to identify the contamination sources of this kind of food are needed to tackle MDR E. coli dissemination. Abstract : Significance and Impact of the Study: This study identified ESBL‐producing Escherichia coli epidemic clones: ST131, ST410 and ST744 in ready‐to‐eat street food samples. Street food is a possible way to spread harm multidrug‐resistant (MDR) E. coli strains in the community. Studies to identify the contamination sources of this kind of food are needed to tackle MDR E. coli dissemination.